Assessing lower limb strength, power and asymmetry in elite soccer players using the Keiser Air420 seated leg press - Redden, J. (University of Bath, 2019)
In soccer, lower limb strength, power and bilateral asymmetry is considered a significant contributor to physical performance and injury risk. Therefore, the monitoring and testing of lower limb physical performance through a practical, applicable and reliable method is of paramount importance to practitioners. The Keiser Air420 seated leg press is a strength and power training and testing tool extensively used in elite soccer, however limited scientific research has been completed to support its use. The current thesis completed investigations to gain a greater understanding. To provide a foundation for subsequent studies, initial research investigated the reliability of elite soccer players using the seated leg press across 3 consecutive trials. `Good` reliability was established for all strength and power variables with bilateral asymmetry variables calculated around the average power values found to be the most reliable measures. Test-retest results also established limits of meaningful change for each variable to accurately evaluate change in longitudinal testing results. Subsequently, typical characteristic lower limb values for an elite soccer player were established with an average bilateral power asymmetry of 4.3±4.1% established. Centre Backs and Strikers were found to have `likely` higher strength, power and asymmetry values than all other positions and U21 playing squad found to have higher Average Power Combined and Velocity Max Combined than the average of all players. Across a soccer season (July to April), the youngest professional squad (U17) showed `likely` small increases in lower limb strength and power whilst U18 and U21 squads remained largely unchanged at all testing points. No significant variation in bilateral asymmetry was seen across a season for any playing squad. When assessing seated leg press performance around match play, no differences in lower limb performance were found immediate post-match with `possible` decreases seen in Peak Power Combined at 24 h post-match when an obvious outlier was excluded. Although no clear differences were seen in bilateral asymmetry, 5 of 19 participants notably increased their asymmetry values both immediately post-match and at 24 h postmatch suggesting large individual variation in response of lower limb strength, power and asymmetry following match participation. Limited effects were seen when comparing pre-season strength, power and bilateral asymmetry values and overall season-long injury incidence. However, clear `likely` and `very likely` harmful effects were seen for increased strength and power variables in relation to injury burden across a season suggesting that stronger, more powerful individuals are at no greater risk of injury incidence but are likely to suffer a greater injury burden if injury occurs. This thesis has provided the applied practitioner with greater confidence and detail regarding the testing of elite soccer players using the Keiser Air420 seated leg press. The identification of typical characteristic values, limits of meaningful change around variables and parameters associated with increased injury burden enable practitioners to use the testing protocol with elite soccer players with greater confidence whilst also gaining greater insight into results found.